Consumer risk perception of online food delivery during the COVID-19 Movement Control Order (MCO) in Malaysia - Poon, Wai Chuen; Tung, Serene En Hui (Taylor & Francis Group, 2022)
Malaysia’s online food delivery (OFD) has developed into a vibrant scene. Urban dwellers are slowly getting used to the idea of OFD services as the new normal for eating out at the times of COVID-19. During the movement control order (MCO), government initiatives and movement restrictions propelled OFD services into the limelight, allowing locals the opportunity to support their favorite local businesses. Using model goal-directed behavior (MGB), this study investigated the effect of consumers’ perceived risk (e.g., performance risk, privacy risk, financial risk, physical risk, and COVID-19 risk) on their use of OFD services. The results of the partial least squares-structural equation modeling (PLS-SEM) analysis of 339 responses indicates that perceived risk negatively affects consumers’ desire to use OFD services, while perceived physical risk and COVID-19 risk negatively affect their intention to use OFD services. Further, the study uncovers the moderating role of perceived risk in the relationship between desire and intention. This study offers insights to OFD service providers in formulating new business strategies and propositions for business growth and consumer retention in the post-pandemic world.